Penggunaan Instrumen Non-Tes dalam Menilai Permasalahan Sosial dan Emosional Siswa : Tinjauan Literatur - Irma Julita; Nurfarhanah; Zadrian Ardi (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Social and emotional problems in students can have a significant impact on their academic development and psychological well-being. Comprehensive assessment of social-emotional aspects is essential in the context of modern education. This article discusses the use of non-test instruments as effective assessment tools to identify social and emotional problems in students. Through a review of current literature, the types, characteristics, advantages, and challenges of using non-test instruments such as observation, interviews, questionnaires, and reflective journals are explained. Implications for the role of teachers and counselors are also examined, with an emphasis on the importance of training and institutional support so that assessment can be carried out optimally. The results of the study indicate that non-test instruments can support a more humanistic holistic assessment approach that is responsive to students' needs. This article recommends the integration of social-emotional assessment into school policies and the improvement of educators' professional capacity as strategic steps in supporting students' sustainable social-emotional development.